Colour Temperature Tuning to Improve Efficacy of White Light. (2016) - Prathap, Saijo; Sunny, Sonia; Nair, Aju S.
Abstract: Quality of white light is always an aspect in lighting application. The white light produced may not be of good quality. Using the MacAdam's ellipse we can produce light near to daylight quality. Using the colour mixing principle in RGB light source, the designed fixture uses a warm white and cool white chip on board LED. The correlated colour temperature and intensity of the lighting is varied using the PWM dimming method. ZigBee based wireless control transmission is used to transmit the PWM signals. Different white light is produced using this set up. The efficacy can be improved along with reduction in power consumption.